Circulative biomarkers as predictors of cardiovascular events in patients after treatment of Hodgkin lymphoma - B. B. Samura (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2017)
Aim. Nature development of lymphoma associates with increased risk of cardiovascular diseases. We aimed to evaluate the prognostic value of circulating NT-proBNP, galectin-3, and VE-cadherin in survivors of Hodgkin lymphoma.